Exploring the strategies used by political parties to build political narratives in Pakistani public: A case study of elections - Awan, Waqas (Pakistan Review of Social Sciences (PRSS), 2023)
Social media has become the most potential and influential source of narrative building and agenda setting among people as an effective tool for political communication today. The multidimensional interaction between politicians and publics have intensified the effects of social media and inculcation of popular political ideas among voters. The proposed study aim to explore consumption patterns of social media (Twitter and Facebook) among political parties and journalists who build narratives and make popular opinion in public. Drawing theoretical foundation from Agenda Setting theory the study will use qualitative research design for data collection. The sample for proposed study will be the social media managers of popular political parties of Pakistan and most followed journalists. The interviews with open ended questions will be used as research method to collect responses from the selected sample. The collected data will be interpreted and analysed in the light of qualitative data analysis techniques.